Bacterially Derived Tryptamine Increases Mucus Release by Activating a Host Receptor in a Mouse Model of Inflammatory Bowel Disease - Yogesh Bhattarai; Si Jie; David R. Linden; Sayak Ghatak; Ruben A.T. Mars; Brianna B. Williams; Meng Pu; Justin L. Sonnenburg; Michael A. Fischbach; Gianrico Farrugia; Lei Sha; Purna C. Kashyap (iScience, 2020)
Summary: Recent studies emphasize the role of microbial metabolites in regulating gastrointestinal (GI) physiology through activation of host receptors, highlighting the potential for inter-kingdom signaling in treating GI disorders. In this study, we show that tryptamine, a tryptophan-derived bacterial metabolite, stimulates mucus release from goblet cells via activation of G-protein-coupled receptor (GPCR) 5-HT4R. Germ-free mice colonized with engineered Bacteroides thetaiotaomicron optimized to produce tryptamine (Trp D+) exhibit decreased weight loss and increased mucus release following dextran sodium sulfate treatment when compared with mice colonized with control B. thetaiotaomicron (Trp D-). Additional beneficial effects in preventing barrier disruption and lower disease activity index were seen only in female mice, highlighting sex-specific effects of the bacterial metabolite. This study demonstrates potential for the precise modulation of mucus release by microbially produced 5-HT4 GPCR agonist as a therapeutic strategy to treat inflammatory conditions of the GI tract.